Haiti's paper war : post-Independence writing, civil war, and the making of the republic, 1804-1954 - Stieber, Chelsea (America and the long 19th century., 2020)
""Haiti's Paper War" explores civil war and post-independence writing in Haiti during the years of 1804-1954"--